Expansion of additive-manufactured tubes: deformation and metallurgical analysis - Pragana, João (2021)
Herein, the mechanical and metallurgical feasibility of integrating tube end-forming operations with additive manufacturing is investigated. The work makes use of wire-arc additively manufactured AISI 316L stainless steel preforms that are subsequently machined into tubes and expanded with a tapered conical punch. Experimental measurements of force, surface strains, thickness, and microhardness combined with microstructure observations and fractography of the fractured surfaces are utilized to characterize plastic deformation and formability limits of the additively manufactured tubes and understand the main differences against the results obtained from commercial wrought tubes of the same material. Results show that the material deformation characteristics, namely, the evolution of microhardness along the expanded tube length, and the formability limits by necking and fracture, are strongly influenced by the columnar microstructure originated by a noncyclic dendritic growth aligned with the building direction. Still, results demonstrate that the additively manufactured AISI 316L tubes are ductile enough to be successfully included in hybrid additive manufacturing routes.